Ultra high energy cosmic rays as a probe of black strings - Anjos, Rita C. (2015)
Ultrahigh energy cosmic rays (UHECRs) are problably originated in extragalactic sources as, e.g., Active Galactic Nuclei (AGNs). In the present work it is proposed an approach to calculate bounds on the AGN luminosity fraction that can be converted in such UHECRs. This result comes from two separated points of view: (i) the intrinsic mechanism powered by central black holes to produce the AGN luminosity and (ii) the observation of UHECRs and gamma-rays from ground experiments to reconstruct proton luminosities of a given AGN source.